ANALYZING LABOR MOBILITY AND MIGRATION IN THE DIGITAL GAMES INDUSTRY: A STUDY WITH BRAZILIAN WORKERS - Rocha, Andre Campos (AoIR Selected Papers of Internet Research, 2026)
This paper investigates the mobility and migration experiences of Brazilian workers in the digital games industry, focusing on issues of digital labor and the political economy of the cultural and technological industries. The research answers questions about the circulation of these workers in the labor market and the relationship between migration and labor process in the games industry. Using industry reports and a literature review, the study is based on 14 semi-structured interviews conducted between October 2022 and August 2024 with key professionals in the production of digital games, such as programmers, artists, designers, and managers. The paper starts from the hypothesis that, in a global labor market, workers from peripheral countries, such as Brazil, have economic incentives to migrate and work for foreign companies, especially in the Global North, where the games industry is more developed. Through Labor Process Theory (LPT), the article: (1) demonstrates that these mobility experiences of these workers are marked by mobility/immobility dynamics, reflecting pronounced global inequalities; (2) exposes the various forms of mediation that facilitate the circulation of these workers in the labor market, including educational institutions, social networks and social media, and events; and (3) investigates the relevance of territory and spatial constraints to understanding the labor process, highlighting local production cultures, work organization, and unionization. The text establishes dialogues with studies of LPT and migration, contributing to the understanding of the relationships between migration and digital labor in the gaming industry.